Use of wearables to measure the effects of long COVID on activities of daily living and their relationship to perceived exertion, occupational performance, and quality of life - Hernández-Hernández, Lucía; Obeso-Benítez, Paula; Serrada-Tejeda, Sergio; Sánchez-Herrera-Baeza, Patricia; Rodríguez-Pérez, Ma Pilar; Pérez-de-Heredia-Torres, Marta; Martínez-Piédrola, Rosa María; Martín-Hernández, Jorge (Frontiers in Public Health, 2025)
IntroductionThis study introduces a novel approach to understanding the impact of long COVID symptoms on daily life by integrating wearable devices to assess their influence on physical and mental quality of life, as well as perceived performance and satisfaction in daily activities.MethodsBy leveraging technology such as accelerometers and pulse oximeters alongside assessment tools like the SF-12 Health Survey, the Canadian Occupational Performance Measure, and the Borg Scale, this research provides a comprehensive analysis that advances the field of occupational therapy.ResultsAn analytical observational study with 10 participants with long COVID and 10 healthy controls revealed that individuals with long COVID took significantly longer to complete tasks such as setting the table, sweeping, and climbing stairs, compared to the control group. Participants with long COVID also reported higher perceived exertion during all activities, as well as significantly worse physical health-related quality of life and lower satisfaction and performance in daily activities. Notably, perceived exertion correlated with reduced physical quality of life and diminished satisfaction and accomplishment in occupational tasks.DiscussionThese findings emphasize the critical need for occupational therapy interventions to reduce perceived exertion, which could improve physical quality of life and enhance performance and satisfaction in daily activities for individuals with long COVID.